2002
DOI: 10.2320/matertrans.43.1676
|View full text |Cite
|
Sign up to set email alerts
|

Two-Way Shape Memory Effect Induced by Bending Deformation in Ductile Cu-Al-Mn Alloys

Abstract: Martensitic transformation temperatures and the two-way shape memory effect (TWME) in ductile Cu-Al-Mn alloys deformed at room temperature were investigated using differential scanning calorimetry (DSC) and the bending test. The M s and A f temperatures were found to increase slightly with increasing degree of pre-deformation, while the M f and A s temperatures decreased. The TWME is strongly influenced by the M s temperature and the grain size of the specimens, i.e., the highest degree of TWME is always obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…d'=dT, is about 2.1 in the same Cu-Al-Mn polycrystalline alloy. 11,12) Therefore, the martensitic transformation temperatures determined by DMS are expected to rise by about 10 C. In the present paper, DMS curves only during the heating process are presented, because the cooling curves show tendencies similar to those of the corresponding heating as demonstrated in Fig. 1.…”
Section: Methodsmentioning
confidence: 91%
“…d'=dT, is about 2.1 in the same Cu-Al-Mn polycrystalline alloy. 11,12) Therefore, the martensitic transformation temperatures determined by DMS are expected to rise by about 10 C. In the present paper, DMS curves only during the heating process are presented, because the cooling curves show tendencies similar to those of the corresponding heating as demonstrated in Fig. 1.…”
Section: Methodsmentioning
confidence: 91%
“…The reason for this difference is not clear, but a similar tendency was observed for the TWM effect induced by bending deformation in the Cu-Al-Mn alloy sheets. 13 The LTE temperature intervals (∆T LTE ), defined as the temperature region where the absolute value of the coefficient of thermal expansion is lower than 3 ϫ 10 Ϫ6 /K, are about 130°C and 150°C for the specimens with mean grain diameters ofd ϭ 0.61 mm and 1.51 mm, respectively ( Fig. 2a and b).…”
Section: Effects Of Grain Size and Specimen Thicknessmentioning
confidence: 99%
“…It is known that the grain refinement, however, causes a decrease of the SM and TWM effects. [10][11][12][13] Figure 2 shows the thermal expansion curves in RD with different reductions of cold rolling for the Cu-22.3Zn-10.6Al (at.%) β single-phase specimens (S alloy in Table I) with different mean grain diameters ofd ϭ 0.61 mm andd ϭ 1.51 mm. It is shown that the transition temperature intervals, i.e., M s Ϫ M f and A f Ϫ A s , increase with increasing reduction ratio, where M s , M f , A s , and A f are defined as temperatures that show minimum curvature in the cooling and heating curves as demonstrated in Fig.…”
Section: Effects Of Grain Size and Specimen Thicknessmentioning
confidence: 99%
“…The two-way shape memory effect (TWSME) associated with the forward and reverse transformations of martensite is a phenomenon in which the reversible and spontaneous shape change during heating and cooling occur without any external stress [1]. The TWSME not only relates to the behavior of martensite transformation in shape memory alloys (SMAs), but also depends on training methods such as superelastic (SE) or shape memory effect (SME) training, thermomechanical training, aging under external stress, etc.…”
Section: Introductionmentioning
confidence: 99%